Answer:
use desmos to graph it
Step-by-step explanation:
heres a picture
Answer:
Step-by-step explanation:
a) <u>Jamal spent:</u>
<u>Isaiah spent:</u>
<u>The equation is:</u>
b) <u>Solving the equation</u>
- 2x = 3x - 6.75
- 3x - 2x = 6.75
- x = 6.75
c) <u>Jamal's items cost </u>
<u>Isaiah's items cost </u>
- $6.75 - $2.25 = $4.50 each
L = 0 bcause it cancels itself out
Just for future reference always put ^ for exponents. The answer is y-6 though.
(y-4)(y-6) create that trinomial. You can prove that by using the FOIL algorithm